Numerical Simulation of Charge Diffusion on the Surface of a Dendrimer Molecule - Andreyev, A. V.; Klymenko, O. V. (ХНУРЭ, 2009)
This work presents the results of numerical simulation of charge transfer within the spherical outer shell of a dendrimer macromolecule induced by electrode polarisation on which the molecule is adsorbed. It is shown that under linear variation of the electrode potential the electric current peak contains information about the regimes of charge diffusion in the molecular shell. Thus the obtained results can be used for the determination of kinetic parameters from experimental data.
Keywords: electrochemistry; dendrimer; surface diffusion; numerical simulation